2013
DOI: 10.1063/1.4794963
|View full text |Cite
|
Sign up to set email alerts
|

Solar photocatalytic oxidation and disinfection of municipal wastewater using advanced oxidation processes based on pH, catalyst dose, and oxidant

Abstract: There are great interests in photocatalytic oxidation of contaminants using advanced oxidation processes (AOP) based on photocatalytic oxidation in recent years. The main aim of the paper is to develop a method which takes care of energy and water conservation together. The study was performed on photocatalytic disinfection of total coliform (TC) bacteria as water microbial pollution and reducing the chemical oxygen demand (COD) as organic pollution index using catalytic and oxidant in present of sun light. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Semiconductor photocatalysis is an efficient and promising green technology that can utilize solar light energy to degrade organic or inorganic pollutants in wastewater treatment. 1,2 A number of traditional photocatalysts, such as titanium dioxide (TiO 2 ) and zinc oxide (ZnO) are only active in ultraviolet light, due to their large intrinsic band gap (3.0-3.2 eV). This results in an inefficient use of solar light or visible light (<5% of the solar spectrum) and, thus restricts their practical application.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor photocatalysis is an efficient and promising green technology that can utilize solar light energy to degrade organic or inorganic pollutants in wastewater treatment. 1,2 A number of traditional photocatalysts, such as titanium dioxide (TiO 2 ) and zinc oxide (ZnO) are only active in ultraviolet light, due to their large intrinsic band gap (3.0-3.2 eV). This results in an inefficient use of solar light or visible light (<5% of the solar spectrum) and, thus restricts their practical application.…”
Section: Introductionmentioning
confidence: 99%
“…The schematic diagram of the photocatalytic system used in our study is reported. 18 It maintains the turbulent conditions and there is no mass transfer limitation. It is a nearly closed system no vaporization of volatile compounds takes place.…”
Section: B Experimental Set-upmentioning
confidence: 99%
“…9 The optimization of the photocatalytic process for several organic contaminants degradation has been carried out, varying the semiconductor concentration, pH, oxidants addition such as peroxides, persulfates, among others. [10][11][12][13][14] In general, the degradation rate constant of the contaminants increases with TiO 2 concentration in heterogeneous photocatalysis. So, it has been considered that the larger the number of active sites to dye adsorption, as well the interaction with electron-hole pairs, the larger the degradation efficiency will be.…”
Section: Introductionmentioning
confidence: 99%